THE WASTE BANK FINANCIAL REPORTS AS BUSINESS DEVELOPMENT IN HOUSING ENVIRONMENT OF LARANGAN MEGA ASRI SIDOARJO - Agustini, Ni Ketut Yulia; Indahwati; Marpurdianto, Kharis (jfpublisher, 2023)
This community service aims to improve the status of a “waste bank” for Small and Medium Enterprises (UMKM). Therefore, preparation was needed, such as evaluating financial statement, then conducting training on compiling financial statement for Small and Medium Enterprises (UMKM). Fikriyyah, S. F., & AdiWibowo (2018; 703) state that a “waste bank” forms a community service that cares for the environment and is expected to increase the income. Thus, the existence of a “waste bank” does not significantly affect household income because the average monthly revenue was about 0.4 % to 0.68%. Therefore, the target of the community service was to evaluate the financial statements of “waste bank” adjusting by compiling financial statement for Small And Medium Enterprises, known as UMKM in Indonesia. Furthermore, this community service has been carried out multi-year, which will continue with entrepreneurship training and preparation for establishing a Small And Medium Enterprises (UMKM) to the “waste bank”.